Individual Values dan Psychological Well-Being Terhadap Komitmen Organisasi - Mubarok, Fikri (TAZKIYA Journal of Psychology, 2019)
This research was conducted to determine internal factors in individuals that influence organizational commitment. This study uses a quantitative approach with multiple regression analysis. A sample of 171 nurses at Cempaka Putih Hospital was taken using a non-probability sampling technique. In this study, the authors modified the instrument, namely the Organizational Commitment Questionnaire (OCQ), Portrait Values Questionnaire (PVQ), and Psychological Well-Being Scale (PWBS). The instrument was tested for its validity using the confirmatory factor analysis (CFA) technique. The results showed that there were individual values and psychological well-being influences on organizational commitment. Self-acceptance and purpose in life have an influence on organizational commitment. Affective commitment dimensions are influenced by self-acceptance. The normative commitment dimension is influenced by positive relations with others, purpose in life, personal growth, and tradition. The continuance commitment dimension is influenced by purpose in life and hedonism. The researcher hopes that the results of this study can be developed in future studies. besides, the researchers hope that further research will be conducted in the context of work other than nurses.